2013
DOI: 10.1002/chem.201303261
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Modification of Platinum by Co‐Adsorbed Cinchonidine and Trifluoroacetic Acid: Origin of Enhanced Stereocontrol in the Hydrogenation of Trifluoroacetophenone

Abstract: Cinchonidine (CD) adsorbed onto a platinum metal catalyst leads to rate acceleration and induces strong stereocontrol in the asymmetric hydrogenation of trifluoroacetophenone. Addition of catalytic amounts of trifluoroacetic acid (TFA) significantly enhances the enantiomeric excess from 50 to 92%. The origin of the enantioselectivity bestowed by co-adsorbed CD and TFA is investigated by using in situ attenuated total reflection infrared spectroscopy and modulation excitation spectroscopy. Molecular interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 90 publications
0
35
0
Order By: Relevance
“…[10] Recently, we investigated the adsorption-desorption behavior of TFAP and CD on the Pt catalyst applying modulation excitation spectroscopy and phase-sensitive detection revealing the formation of a diastereomeric complex between TFAP and CD involving a N À H À O-type hydrogen bond. [11] In another in situ spectroscopic study on the asymmetric hydrogenation of KPL, we found evidence for an additional stereodirecting interaction between the alcoholic OH group of CD and a carbonyl C=O group of the cyclic a ketoester, which appears to be relevant for explaining the excellent enantioselection achieved with this substrate. [12] While these in situ IR studies have been carried out in a similar chemical environment as encountered in the catalytic reaction, the methods applied captured only a snapshot of the surface at quasi-steady state and neither measurable catalytic turnover nor optical yield could be observed.…”
mentioning
confidence: 73%
“…[10] Recently, we investigated the adsorption-desorption behavior of TFAP and CD on the Pt catalyst applying modulation excitation spectroscopy and phase-sensitive detection revealing the formation of a diastereomeric complex between TFAP and CD involving a N À H À O-type hydrogen bond. [11] In another in situ spectroscopic study on the asymmetric hydrogenation of KPL, we found evidence for an additional stereodirecting interaction between the alcoholic OH group of CD and a carbonyl C=O group of the cyclic a ketoester, which appears to be relevant for explaining the excellent enantioselection achieved with this substrate. [12] While these in situ IR studies have been carried out in a similar chemical environment as encountered in the catalytic reaction, the methods applied captured only a snapshot of the surface at quasi-steady state and neither measurable catalytic turnover nor optical yield could be observed.…”
mentioning
confidence: 73%
“…Protic solvents lead to the protonation of the nucleophilic quinuclidine N atom of cinchona alkaloids, which is involved in the N-HÁ Á ÁO binding of the modifier-substrate complex. 50 Crucial molecular interactions between the chiral modifier (CD), acid additive (TFA) and the reactant trifluoroacetophenone at the catalyst surface were elucidated under reaction conditions. Fig.…”
Section: Interactions With Solvents or Additivesmentioning
confidence: 99%
“…Up to date, most mechanistic studies of the surface processes relevant to asymmetric hydrogenation on chirally modified platinum catalysts have been carried out ex situ9 or under conditions relatively far from those encountered in practice 10. Recently, we investigated the adsorption–desorption behavior of TFAP and CD on the Pt catalyst applying modulation excitation spectroscopy and phase‐sensitive detection revealing the formation of a diastereomeric complex between TFAP and CD involving a NHO‐type hydrogen bond 11. In another in situ spectroscopic study on the asymmetric hydrogenation of KPL, we found evidence for an additional stereodirecting interaction between the alcoholic OH group of CD and a carbonyl CO group of the cyclic α ketoester, which appears to be relevant for explaining the excellent enantioselection achieved with this substrate 12.…”
Section: Methodsmentioning
confidence: 99%